Pengaruh Penggunaan Smartphone terhadap Motivasi Belajar Siswa SMA di Kp. Pasirsalam - Ikhsan, Dzikril; Kuntari, Septi (Lembaga Yasin AlSys, 2022)
This study aims to determine the effect of smartphone use on students' learning motivation in Kp. Pasirsalam. Lebak Regency, Banten Province. Researchers used a quantitative approach with the population in this study, namely students who live in Kampung Pasirsalam and are still studying at the high school level, totaling 21 people. The sample used in this study is all the population with a total of 21 students, because it uses a saturated sampling technique as the sample. Collecting data using a questionnaire or questionnaire distributed to students who are still studying at the high school level in Kp. Pasirsalam, using simple linear regression analysis. The results of hypothesis testing are obtained as follows: 1) There is a significant effect between smartphone use and learning motivation. This is evidenced by the value of sig. = 0.002 < 0.05 and F count = 7.692